Identification of candidate genes associated with host-seeking behavior in the parasitoid wasp Diachasmimorpha longicaudata - Wulff, Juan Pedro (2024)
Background: Diachasmimorpha longicaudata is a hymenopteran fruit fly endoparasitoid. Females of this species find their hosts for oviposition by using complex sensorial mechanisms in response to physical and chemical stimuli associated with the host and host habitat. Ecological and behavioral aspects related to host-seeking behavior for oviposition have been extensively studied in D. longicaudata, including the identification of volatile organic compounds acting as attractants to females. In this sense, molecular mechanisms of chemoreception have been explored in this species, including a preliminary characterization of odorant-binding proteins (OBPs), chemosensory proteins (CSPs) and odorant receptors (ORs), among other proteins. Functional assays on OBP and CSP have been conducted as a first approach to identify molecular mechanisms associated with the female host-seeking behavior for oviposition. The aims of the present study were to identify the D. longicaudata sensory gene repertoire expressed in the antenna of sexually mature and mated individuals of both sexes, and subsequently, characterize transcripts differentially expressed in the antennae of females to identify candidate genes associated with the female host-seeking behavior for oviposition. Results: A total of 33,745 predicted protein-coding sequences were obtained from a de novo antennal transcriptome assembly. Ten sensory-related gene families were annotated as follows: 222 ORs, 44 ionotropic receptors (IRs), 25 gustatory receptors (GRs), 9 CSPs, 13 OBPs, 2 ammonium transporters (AMTs), 8 pickpocket (PPKs) receptors, 16 transient receptor potential (TRP) channels, 12 CD36/SNMPs and 3 Niemann-Pick type C2 like proteins (NPC2-like). The differential expression analysis revealed 237 and 151 transcripts up- and downregulated, respectively, between the female and male antennae. Ninety-seven differentially expressed transcripts corresponded to sensory-related genes including 88 transcripts being upregulated (87 ORs and one TRP) and nine downregulated (six ORs, two CSPs and one OBP) in females compared to males. Conclusions: The sensory gene repertoire of D. longicaudata was similar to that of other taxonomically related parasitoid wasps. We identified a high number of ORs upregulated in the female antenna. These results may indicate that this gene family has a central role in the chemoreception of sexually mature females during the search for hosts and host habitats for reproductive purposes.